2011
DOI: 10.1128/iai.00983-10
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Mediated Intracellular Growth Restriction of Pathogenic Rhodococcus equi Can Be Prevented by Iron

Abstract: Rhodococcus equi is an intracellular pathogen which causes pneumonia in young horses and in immunocompromised humans. R. equi arrests phagosome maturation in macrophages at a prephagolysosome stage and grows inside a privileged compartment. Here, we show that, in murine macrophages activated with gamma interferon and lipopolysaccharide, R. equi does not multiply but stays viable for at least 24 h. Whereas infection control of other intracellular pathogens by activated macrophages is executed by enhanced phagos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…2 hr of infection. Phagosomes containing strain 103− steadily acidify to a pH of 5.0 (von Bargen, Wohlmann, Taylor, Utermöhlen, & Haas, 2011). We now show that the pH of phagosomes containing strain ΔvapA decreases quickly to~5.8 and does not show any pH rebound as with phagosomes containing strain 103+ ( Figure 5d).…”
Section: Vapa Is Responsible For Ph Neutralisation and Exclusion Ofmentioning
confidence: 53%
See 2 more Smart Citations
“…2 hr of infection. Phagosomes containing strain 103− steadily acidify to a pH of 5.0 (von Bargen, Wohlmann, Taylor, Utermöhlen, & Haas, 2011). We now show that the pH of phagosomes containing strain ΔvapA decreases quickly to~5.8 and does not show any pH rebound as with phagosomes containing strain 103+ ( Figure 5d).…”
Section: Vapa Is Responsible For Ph Neutralisation and Exclusion Ofmentioning
confidence: 53%
“…Multiplication of virulent strain 103+ was not affected by addition of rVapA ( Figure S7A) indicating that virulent R. equi produce saturating amounts of VapA. It also argues that the extra rVapA does not interfere with multiplication of virulent R. equi, for example, by damaging or activating macrophages which, in turn, could kill R. equi (von Bargen et al, 2011). Of note, the vacuoles, which contained avirulent strain 103− in rVapA-fed cells at 24 hr of infection were packed with vesicular cargo ( Figure S7B) and thus also revealed the typical complex RCV pattern (compare Figures S6B and S7C).…”
Section: Preventing Acidification Is the Major Virulence Mechanism mentioning
confidence: 96%
See 1 more Smart Citation
“…However, the true identity of Toxo1 has not been confirmed. A large number of reports have demonstrated that nitric oxide (NO) is a major effector molecule for macrophage-mediated cytotoxicity in mouse macrophages and is a key anti-pathogen factor used by the infected host to control progression of intracellular pathogens including Toxoplasma (Adams et al, 1990;Davis et al, 2007;EI Kasmi et al, 2008;James, 1995;Von Bargen et al, 2011). Recent evidence indicates that the high expression of inducible nitric oxide synthase (iNOS), which is also located on chromosome 10, and low expression of Arg-1 in the macrophages of rats are strongly linked to this resistance when T. gondii RH strain was used to infect the cells (Li et al, 2012;Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors determined that macrophage activation results in Fe 2+ depletion that can be compensated by external supplementation in the medium. Restoring R. equi access to Fe 2+ fully reversed the growth‐inhibitory effects of RNI .…”
Section: A Whole Palette Of Saltsmentioning
confidence: 95%